Effectiveness of Risk Analysis Index Frailty Scores as a Predictor of Adverse Outcomes in Lower Extremity Reconstruction - Swiekatowski, Kylie R.; Barrera, Jose E.; Hopkins, David; Manisundaram, Arvind D.; Bhadkamkar, Mohin A.; Wu-Fienberg, Yuewei (Journal of Reconstructive Microsurgery, 2024)
Background The rising clinical importance of assessing frailty is driven by its predictive capability for postoperative outcomes. This study assesses the effectiveness of RAI-rev (Revised Risk Analysis Index) in predicting adverse outcomes in lower extremity (LE) flap reconstruction.Methods Analyzing NSQIP (National Surgical Quality Improvement Program) data from 2015 to 2020, we compared demographics, perioperative factors, and 30-day outcomes in all locoregional and free-flap cases. Frailty scores, calculated using RAI-rev, were categorized with <15 as nonfrail and >35 as the most frail. Adjusted odds ratios (aORs) for specific complications were calculated using nonfrail as the reference group. Frailty scores in locoregional flaps were compared with those in free flaps.Results We identified 270 locoregional and 107 free-flap cases. Higher RAI-rev scores in locoregional flaps correlated with increased complications, such as deep surgical site infection (1% nonfrail vs. 20% RAI 31–35), stroke (0% nonfrail vs. 17% most frail), and mortality (0% nonfrail vs. 17% most frail). Locoregional flap cases with RAI-rev scores in the most frail group had a significantly elevated aOR for stroke (51.0, 95% confidence interval [CI]: 1.8–1402.5, p = 0.02), mortality (43.1, 95% CI: 1.6–1167.6, p = 0.03), and any complication (6.8, 95% CI: 1.2–37.4, p = 0.03). In free-flap cases, higher RAI-rev scores were associated with increased complications, with only sepsis showing a statistically significant difference (6% nonfrail vs. 100% most frail; aOR: 42.3, CI: 1.45–1245.3, p = 0.03). Free-flap cases had a significantly lower RAI-rev score compared with locoregional flap cases (14.91 vs. 17.64, p = 0.01).Conclusion Elevated RAI-rev scores (>35) correlated with more complications in locoregional flaps, while free-flap reconstruction patients had generally low RAI-rev scores. This suggests that free flaps are less commonly recommended for presumed higher risk patients. The study demonstrates that RAI-rev may be able to serve as a risk calculator in LE reconstruction, aiding in the assessment of candidates for limb salvage versus amputation.
Keywords: lower extremity; limb salvage; frailty